Problem of radon exposure in energy-efficient buildings: a review - Ilya V. Yarmoshenko; Georgy P. Malinovsky; Aleksandra D. Onishchenko; Aleksey V. Vasilyev (Радиационная гигиена)
The paper presents an overview of the international scientific and technical publications on a problem of radon accumulation in new energy efficient buildings and in houses reconstructed according to requirements of energy saving. Energy efficiency is an important requirement of the environmentally sustainable development. Housing and communal services have significant potential for energy saving. In Russia, the construction of highest energy efficiency classes buildings occurs at an accelerated rate and reached 75% of all multiapartment houses built in 2017. The applying of modern technologies that reduce heat loss is accompanied by a decrease in the air exchange rate, which leads to deterioration of indoor air quality, in particular, the accumulation of radon. In the international literature, there are examples of the several times growth of radon concentration after the reconstruction of the building, the average radon concentration in retrofitted buildings increased by 22–120%. In new houses built to meet energy saving requirements, there can also be a significant increase in radon concentration compared to low-energy efficiency classes houses. Excess of sanitary and hygienic norms was found in some countries, including Russia. Radon exposure of dwellers of energy-efficient buildings is largely determined by the living habits. Based on the review data, it can be assumed that the average level of Russian population exposure to radon can increase under conditions of intensive construction of energy-efficient buildings.